2020
DOI: 10.1021/jacs.0c08691
|View full text |Cite
|
Sign up to set email alerts
|

Do Aptamers Always Bind? The Need for a Multifaceted Analytical Approach When Demonstrating Binding Affinity between Aptamer and Low Molecular Weight Compounds

Abstract: Since their inception, DNA aptamers were regarded as the turning point for biochemical sensing in real samples; however up to now their promises are far from being fulfilled. Especially aptamers for small molecules pose a challenge for both selection and characterization. The lack of a universally accepted and robust quality control protocol for the characterization of aptamer performances coupled with the observation of inconsistent data sets in literature, prompted us to address the issue comparing different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 65 publications
(145 reference statements)
0
64
0
Order By: Relevance
“…However, truncation cannot be done by simply removing the fixed primer binding regions without confirming binding. We recently found that the truncated chloramphenicol aptamer cannot bind chloramphenicol, [119] and Bottari et al confirmed that the ampicillin aptamer cannot bind the intended target either [120] . Based on sequence alignment, mutation of one or a few critical nucleotides should fully abolish binding without changing the overall secondary structure of aptamers.…”
Section: Is It An Aptamer?mentioning
confidence: 99%
“…However, truncation cannot be done by simply removing the fixed primer binding regions without confirming binding. We recently found that the truncated chloramphenicol aptamer cannot bind chloramphenicol, [119] and Bottari et al confirmed that the ampicillin aptamer cannot bind the intended target either [120] . Based on sequence alignment, mutation of one or a few critical nucleotides should fully abolish binding without changing the overall secondary structure of aptamers.…”
Section: Is It An Aptamer?mentioning
confidence: 99%
“…Since Apt2 is shorter and has reliable binding, and structure‐switching property, it is recommended for future use. Recently, a number of aptamers were reported to be unable to bind their targets after careful binding assays, such as those for As(III), [38] ampicillin, [39] and chloramphenicol [40] . The Apt1 for dopamine was also studied on electrode surface for binding [20] with negative results.…”
Section: Discussionmentioning
confidence: 99%
“…As recently argued by Wu et al [ 42 ], there is an urgent need to go beyond the “proof of concept,” exploring the real potentialities and limitations of aptamers as bioreceptors when facing analytical problems. Although thousands of papers have been published on aptamers, a rigorous multifaceted characterization of aptamer–target structures and the binding mechanism is still lacking, which would be critical for assessing the reliability of aptamers as bioreceptors [ 42 , 43 ]. The scientific community is urgently called to fill the gap between aptamer selection and biosensing strategies, since unfortunately the risk to misinterpret the real performance of an aptamer sequence is high.…”
Section: Open Questions and Challenges To Be Addressedmentioning
confidence: 99%
“…In many cases, aptamer binding assays are not straightforward and can be prone to artifacts [ 19 ]. In this regard, it should be noted that two very recent studies disproved that some oligonucleotide sequences, widely used in literature for the development of aptasensors, do not actually bind to their expected target [ 43 , 44 ]. A multi-technique platform used to characterize the aptamer–target interaction allowed demonstrating that arsenic-binding aptamer, previously used in more than two dozen papers, did not provide a specific binding of As(III), and the same binding trends were observed with a random DNA [ 44 ].…”
Section: Open Questions and Challenges To Be Addressedmentioning
confidence: 99%